(untitled) (مجلة ديالى للبحوث الانسانية, 2025)
This study focuses on the role of Muslim women in the United Kingdom, particularly in the aftermath of 9/11 in the West, When it was swept with anti-Muslim sentiment, the novelist Monica Ali experienced a rise in Islamophobia. The novel Brick Lane (2003), which she wrote based on her own experiences, can be considered an accurate portrayal of many people who were held accountable for crimes committed in the name of Islam. As a result of these events, many innocent Muslims are being targeted for crimes committed by others. What reveals the bitter experience of ordinary Bangladeshi Muslim immigrants who struggled with identity crises in a multicultural, highly educated society. It also reflects the writer’s personal experiences as a Bangladeshi living in the West. The novel was evaluated by examining the Muslim immigrant characters and their various conditions in London. Moreover, the point is that Muslim people in South Asian countries like India, Pakistan, Bangladesh, Nepal, Sri Lanka, and Afghanistan prefer to live and work in the West for a better standard of living, education, and job prospects .